Zonificación de Tiempos de Respuesta en el Transporte Asistencial de Víctimas de Paro Cardiorrespiratorio en el Municipio de Zipaquirá - Rincón Torres, Diego Alejandro (Universidad Antonio Nariño, 2024)
The project focuses on zoning response times for prehospital care for victims of cardiac arrest in the municipality of Zipaquirá through a network analysis. Three service areas have been identified representing different levels of TAP response times, with approximately 61% of the accessible urban perimeter in 5 minutes or less, an additional 38% in 10 minutes or less, and 0.8% in 15 minutes or less. It was also confirmed that 23 out of 24 high-traffic areas in the municipality fall within the 5-minute or less response area. These results have a significant impact on the strategic allocation of future resources and the improvement of APH.